HUBUNGAN PEMBERIAN SUSU FORMULA DENGAN KEJADIAN DIARE PADA BAYI USIA 1-6 BULAN DI DESA TAMBAK CEKUR KECAMATAN SERBAJADI KABUPATEN SERDANG BEDAGAI TAHUN 2019 - Kardina Hayati; Grace Elizabeth Simanullang (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2019)
Formula milk was a type of prelactal food that was often given to neonates before breast milk comes out. Giving formula milk that was not good can increase the risk of diarrhea in infants because the brewing process was too thick and the way to store formula milk was wrong. The purpose of this study was to find out the relationship between the way of serving formula milk with diarrhea events in Tambak Cekur Village, Serbajadi District, Serdang Bedagai Regency in 2019. The type of research conducted in this study was non-experimental, namely collecting data or observations simultaneously between independent variables and dependent variables. by using the Total Sampling method with a sample of 20 respondents Data collection using a questionnaire given to respondents and using Chi Square test data analysis. The results obtained were p value (0.001) < (0.05) or p value = 0.34 which means there was a relationship between the way of serving formula milk with the incidence of diarrhea in infants aged 0-6 months in Tambur Tambur, Serbajadi District, Serdang Bedagai Regency, Year 2019. Infants given formula milk did not provide protection, while diarrhea occurs from infants who were given formula milk. It was hoped that medical staff working at the puskesmas will know how to prepared formula milk to babies to avoid diarrhea. Keywords: Formula milk, Diarrhe, Infants